2012
DOI: 10.3109/09638288.2012.737079
|View full text |Cite
|
Sign up to set email alerts
|

“The final piece of the puzzle to fit in”: an interpretative phenomenological analysis of the return to employment in New Zealand after spinal cord injury

Abstract: For persons employed pre-SCI, we posit that employment identity modification is part of the return to employment process, alongside a supportive social context and networks, and adapted work environments. VR professionals may facilitate return to employment through understanding and fostering the process of employment identity modification and supporting clients to find work opportunities congruent with employment identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 22 publications
1
57
0
Order By: Relevance
“…Being given 'token' work which requires little training or skill is an issue emphasised by people in this population who report feeling insulted and belittled as a result of being assigned such tasks. 23 Thus it appears that job satisfaction, or perceived potential for satisfaction, has a possibly mediating role in enhancing rehabilitation outcomes and facilitating employment post SCI and so should be investigated empirically.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being given 'token' work which requires little training or skill is an issue emphasised by people in this population who report feeling insulted and belittled as a result of being assigned such tasks. 23 Thus it appears that job satisfaction, or perceived potential for satisfaction, has a possibly mediating role in enhancing rehabilitation outcomes and facilitating employment post SCI and so should be investigated empirically.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…22 This is despite the fact that work is viewed by people with SCI as being a central part of returning to a normal life. 14,23 Conventional wisdom generally holds that vocational considerations are inappropriate in the primary rehabilitation phase due to the significant physical and psychosocial adjustment process a person must undertake.…”
Section: Early Interventionmentioning
confidence: 99%
“…Social supports and an appropriate work place are important factors in the return to employment process. 24 Botticello et al showed that employment leads to social participation, but the feasibility of employment depends on variations in regional economic conditions. 1 Krause et al evaluated the association of employment levels and the risk of mortality in persons with SCI.…”
Section: Khazaeipour Et Al Psychosocial Outcomes Following Sci In Iranmentioning
confidence: 99%
“…[1][2][3] This is also true for people who live with heart failure. Heart failure is a chronic progressive condition caused by an inability of the heart to deliver a required amount of oxygenated blood to the body's cells and tissues.…”
Section: Introductionmentioning
confidence: 96%